Global Attractor of Solutions of a Rational System in the Plane - Miron B. Bekker; Martin J. Bohner; Hristo D. Voulov (Discrete Dynamics in Nature and Society)
We consider a two-dimensional autonomous system of rational difference equations with three positive parameters. It was conjectured that every positive solution of this system converges to a finite limit. Here we confirm this conjecture, subject to an additional assumption.